SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-2267
|View full text |Cite
|
Sign up to set email alerts
|

Injection Strategies for Isobaric Combustion

Abstract: In a previous study, we demonstrated that the isobaric combustion cycle, achieved with a split injection strategy, can be more suitable for the double compression expansion engine concept than the conventional diesel combustion cycle. The present work is focused on understanding the effect of different injection strategies on the heat release, efficiency, and emissions of isobaric combustion at the peak cylinder pressure of 150 bar. In situ injection rate measurements are performed to improve our understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Figure 5. Estimation of the delay between the measured signal and the actual injection due to a finite distance between the sensing element and the injector nozzle [4].…”
Section: Compensation For the Outlet-target Distancementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5. Estimation of the delay between the measured signal and the actual injection due to a finite distance between the sensing element and the injector nozzle [4].…”
Section: Compensation For the Outlet-target Distancementioning
confidence: 99%
“…In addition, Nehmer and Reitz [3] studied the effect of injection strategy on soot and NOx formation in a diesel engine and demonstrated significant reductions of these emissions. Babayev et al [4][5] also studied different injection strategies and their effects on the combustion characteristics. In particular, constant-pressure combustion, which was proven superior to the conventional diesel combustion, required complex injection strategies with multiple main injection events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the excessive pressure (up to 300 bar) in the HP unit, it is desirable for the DCEE concept to adopt an isobaric combustion strategy instead of a typically preferred isochoric combustion strategy [18,19]. Okamoto and Uchida's work [20] has shown that it is possible to realize isobaric combustion using three injectors.…”
mentioning
confidence: 99%
“…The previous studies related to the isobaric combustion strategy are mostly focused on experimental or 1D simulation research [5,18]. Therefore, this work intends to further enhance our understanding of the isobaric combustion strategy using the three-dimensional (3D) computational dynamics fluid (CFD) approach.…”
mentioning
confidence: 99%